EFL STUDENTS’ PERCEPTION TOWARDS THE USE OF BAHASA INDONESIA IN AN ENGLISH CLASSROOM - Setya Resmini (Eltin Journal : Journal of English Language Teaching in Indonesia, 2019)
ABSTRACTThe issue of using first language (L1) in teaching English has always been a controversy in the field of teaching and learning English.  The purpose of this study was to investigate the English as Foreign Language (EFL) students’ perceptions towards the use of L1 (Bahasa Indonesia) in the English classroom. In this study, the descriptive qualitative method was employed.  The participants involved in this study are 40 EFL students in the second semester who learn General English in IKIP Siliwangi. A questionnaire which consists of 15 questions was distributed to the participants to gain primary data. To support the data from questionnaire, observation also conducted in the classroom. The findings reveal that the teacher’s use of bahasa Indonesia brought positive/negative perceptions towards students. The students give negative perception towards the teacher’s use of bahasa Indonesia in General English classroom. However, the students also recognized the advantages and disadvantages of the teacher’s use of bahasa Indonesia in the classroom.Key words: EFL; students’ perception; first language (L1); foreign language